Neurosensory development of the four brainstem-projecting sensory systems and their integration in the telencephalon - Fritzsch, Bernd; Elliott, Karen L.; Yamoah, Ebenezer N. (Frontiers in Neural Circuits, 2022)
Somatosensory, taste, vestibular, and auditory information is first processed in the brainstem. From the brainstem, the respective information is relayed to specific regions within the cortex, where these inputs are further processed and integrated with other sensory systems to provide a comprehensive sensory experience. We provide the organization, genetics, and various neuronal connections of four sensory systems: trigeminal, taste, vestibular, and auditory systems. The development of trigeminal fibers is comparable to many sensory systems that project bilaterally from the brainstem or spinal cord to the telencephalon. Taste bud information is primarily projected ipsilaterally through the thalamus to reach the insula. The vestibular fibers develop a bilateral connection that eventually reaches multiple areas of the cortex to provide a complex map. The auditory fibers project in a tonotopic organization to the auditory cortex. The trigeminal and auditory projections maintain a spatial or tonotopic organization, unlike the taste and vestibular systems in the cortex. The individual sensory projections within the cortex provide a multisensory integration in the telencephalon that depends on context-dependent tertiary connections to integrate other cortical sensory systems across the four modalities.